Seasonal influenza vaccination coverage and barriers among healthcare workers in an Egyptian Province - Waheed, Amani; Waheeb, Youssef; Hassan, Adel; Fahim, Ayman (La Medicina del Lavoro, 2020)
Background: Influenza vaccination uptake by Egyptian healthcare workers remains sub-optimal despite local initiatives and infection control programs to increase it. Objective: To assess vaccination coverage and investigate health care workers’ barriers and also motivators toward seasonal influenza vaccination. Methods: An interview questionnaire survey and focus group sessions were conducted to measure uptake and assess barriers to seasonal influenza vaccination among HCWs in main hospitals and primary care centers in Ismailia city. Results: There were 980 participants, of whom 131 (13.4%) reported having received influenza vaccination in last season 2018/2019. Females were 76.8% of participants, and nurses were the main occupational category of study sample (80.4%). The most commonly reported motivator (97.7%) was “protection of oneself and family members” among the vaccinated participants. The top barriers among non-vaccinated ranked by their Relative Importance Index (RII), included lack of instruction by supervisors RII=0.82, lack of awareness about vaccine benefits RII= 0.79 and lack of awareness from where to get the vaccine RII=0.71. Predictors of non-vaccination included belief that the vaccine itself may induce influenza (OR: 1.9 p<0.05, CI, 1.3-2.8) and the perception that vaccination is ineffective (OR: 2.8 p<0.05, CI, 1.5-5.2), and lack of knowledge about the vaccinations recommended for health care workers (OR: 1.9 p<0.05, CI, 1.2-2.8). Conclusions: Addressing specific barriers to influenza vaccination uptake among healthcare workers may improve vaccination rate. Targeted evidence-based promotion campaigns and programs should be established to overcome identified barriers.